Contextualizing international strategy by emerging market firms: A composition-based approach - Luo, Yadong; Bu, J. (Pergamon, 2015)
We present a composition-based logic toward international expansion by emerging market firms (EMFs) - firms that use compositional investment, compositional competition, and compositional collaboration to create a unique competitive advantage in global competition. This view explains how EMFs creatively adopt a composition-based international strategy, enabling them to compensate for their weaknesses while capitalizing on their strengths during global competition where they offer a competitive price-value ratio suited to mass global customers who are cost sensitive. We also explicated the working conditions (i.e., strategic resource-seeking motivation, subsidiary autonomy delegation, and cross-border sharing system) that fortify the outcome of composition. Using survey data from 201 EMFs, our analysis supports these key arguments. A composition-based lens provides a new understanding of why and how emerging market businesses can survive in international competition for some period of time without possessing traditionally defined monopolistic advantages.